Prevalence of prescribed benzodiazepine long-term use in the French general population according to sociodemographic and clinical factors: findings from the CONSTANCES cohort - Guillaume Airagnes; Cédric Lemogne; Adeline Renuy; Marcel Goldberg; Nicolas Hoertel; Yves Roquelaure; Frédéric Limosin; Marie Zins (BMC, 2019)
Abstract Background Data are lacking regarding the prevalence of benzodiazepine long-term use in the general population. Our aim was to examine the prevalence of prescribed benzodiazepine long-term use (BLTU) according to sociodemographic and clinical factors in the French general population. Methods Data came from 4686 men and 4849 women included in 2015 in the French population-based CONSTANCES cohort. BLTU was examined using drug reimbursement administrative registries from 2009 to 2015. Analyses were weighted to provide results representative of the French general population covered by the general health insurance scheme. Weighted prevalence of BTLU and weighted Odds Ratios (OR) of having BTLU were computed with their 95% Confidence Interval (95% CI) according to age, education level, occupational status, occupational grade, household income, marital status, alcohol use disorder risk and depressive symptoms. All the analyses were stratified for gender. Results Weighted prevalence of BLTU were 2.8%(95% CI:2.3-3.4) and 3.8%(95% CI: 3.3-4.5) in men and women, respectively. Compared to men, women had an increased risk of having benzodiazepine long-term use with OR = 1.34(95% CI = 1.02-1.76). Aging, low education, not being at-work, low occupational grade, low income, being alone and depressive state were associated with increased risks of having BTLU. Conclusions BLTU is widespread in the French general population, however this issue may particularly concern vulnerable subgroups. These findings may help in raising attention on this public health burden as well as targeting specific at-risk subgroups in preventive intervention.